Genetic diversity and clinical impact of human rhinoviruses in hospitalized and outpatient children with acute respiratory infection, Argentina - Marcone, Débora Natalia (2014)
BACKGROUND: Human rhinoviruses (HRV) are recognized as a cause of upper and lower acute respiratory infections (ARI). The circulating species and their clinical impact were not described in Argentina. OBJECTIVES: To describe the molecular epidemiology of HRV in children and to determine the association of HRV species with outcome and severity. STUDY DESIGN: Hospitalized and outpatients children <6 years old with ARI without comorbidities (n=620) were enrolled (2008-2010). Demographic, clinical data and outcome were analyzed. HRV were identified by RT-PCR. Phylogenetic analysis and demographic reconstruction for HRV were performed in selected samples. RESULTS: HRV were detected in 252/620 (40.6%) of children; 8.5% in viral coinfection. Bronchiolitis (55%) and pneumonia (13%) were the most frequent clinical diagnosis. Of 202 inpatients with HRV: 72% required oxygen supplementation, 11% intensive care unit and 3% mechanical ventilation. HRV were identified as a risk factor for hospitalization (OR: 2.47). All three HRV species were detected being HRV-A (55%) and HRV-C (43%) the most frequent; HRV-B was infrequent (2%). Of 44 sequenced HRV, 30 genotypes were detected. Seven of them were the most prevalent and circulated during limited periods of time. The demographic reconstruction revealed a constant population size and a high turnover rate of genotypes. Demographic and clinical outcome were similar for HRV-A and HRV-C infections. CONCLUSION: This study highlights the clinical impact of HRV in children without comorbidities as a cause of lower ARI and hospitalization. The high frequency of HRV infections may be associated with the simultaneous circulation of genotypes and their high turnover rate.